Konsep Garapan Tari Cita di Tengah Tekanan Terhadap Budaya Patriarki Dalam Film Yuni Karya Kamila Andini - Andini, Rahma (PPSDP Undergraduate Journal of Educational Sciences, 2025)
Yuni’s film tells the story of the struggle of a woman who wants to achieve her goal of getting her own rights and freedom of choice. In the village where he lives, there are still very strong traditions and social norms. Here the choreographer highlights the process of creating the dance “Cita di Tengah Tekanan”. By analyzing the role of dance movements in strengthening characterization, themes and emotional messages in films. In the story of the film Yuni, work is used not only as an aesthetic element, but also as an in-depth narrative tool to depict the inner turmoil and process of searching for the identity of the main character, Yuni. The concept of creating a dance involves stages of exploration and collaboration that together create dance movements that are in harmony with the storyline and emotions of the characters. With this approach, dance movements not only function as entertainment, but also as a complex medium of expression, bringing stories to life through body movements. The working method used is a dramatic and traditional element. This research is a qualitative descriptive study which aims to find out how the process of creating the dance “Cita di Tengah Tekanan” relates to the party culture in Kamila Andini’s film Yuni. The results of the analysis show that the use of dance in the film Yuni has a significant contribution in strengthening the visual narrative and enriching the emotional experience of the audience.